The Effect of Toxoplasma gondii Parasitic Infection on the Growth and Development of Fetuses in Pregnant Women (Journal of the College of Basic Education, 2026)
This study aimed to determine the prevalence of toxoplasmosis in pregnant women and its adverse effects on pregnancy outcomes in women infected with Toxoplasma gondii IgM in Tikrit, Iraq. The samples were gathered and examined for Toxoplasma IgM antibodies. Pregnancy outcomes were investigated among both infected and non-infected women.The results showed that the prevalence of positive Toxoplasma IgM among pregnant women was 19.4%. The occurrences of abortion, stillbirth, preterm delivery, fetal growth restriction (FGR), and congenital malformation in the infected group were 6 cases (17.1%), 5 cases (14.3%), 3 cases (8.6%), 3 cases (8.6%), and 2 cases (5.7%), respectively. In contrast, the incidences in the control group were 2 cases (2.7%), 2 cases (1.8%), 1 case (0.9%), 1 case (0.9%), and no malformations at (P < 0.01).The study concluded that toxoplasmosis infection may lead to abnormal pregnancy outcomes. Therefore, healthcare institutions should enhance awareness regarding the prevention and treatment of toxoplasmosis and encourage healthy dietary habits among women of reproductive age.